Tuhan dalam Perspektif Ibn Ṭufayl - Muhammad Usman (ILMU USHULUDDIN, 2017)
This  paper aims to analyze Ibn Ṭufayl’s thought of God  in his book, Risālah fī Asrār al-Ḥikmah al- Masyrīqiyyah Ḥayy ibn Yaqzhān (1978, Published Beirut). In the view of Ibn Ṭufayl, God is something that is Al-Maujud that must exist, so that to worship with Al-Maujud is required There is sensitivity of the five senses, rational powers and strong spiritual processes as Ibn Ṭufayl said, in the search for al-Maujud There must be Ibn Ṭufayl using the facilities of the universe such as sky, animals and plants to resemble al-Mawjud that must exist so that in tasyabbuhat (imitating the behavior of nature) ibn Ṭufayl can get a way of illuminating the light of all light and finally it can -musyahadah (witnessing) the essence of God which is the culmination of happiness.